Editorial Pointers. - Crawford, Diane (Communications of the ACM, 2006)
This section presents an overview of the articles in this issue, which focus on the software product line (SPL) method of software creation. This issue contains a special section examining the risks and rewards of SPL. Another article discusses the possible future use of RFID tags in global currencies. Another section presents the recipients of the ACM Distinguished Members award.